The Effect Of Storage Duration And Variance Temperature On High Blend Level Biodiesel Fuel Properties - Mohamad Yusof, Humairak (2017)
Biodiesel is one of the alternative fuels that have been studied to overcome the problem of depleting fossil fuel and its impact on the environment. Biodiesel also has high potential as engine cleaning agent as well as reducing harmful exhaust emissions from combustion process. The objectives of this study are to investigate the effect of High Blend Level (HBL) biodiesel properties and the degradation of HBL biodiesel in certain storage duration and temperature. This study also analysed the potential of running the HBL biodiesel on a diesel engine. Four blend levels of biodiesel are selected from B70, B80, B90 and B5. The properties of biodiesel were investigated according to American Society for Testing and Materials (ASTM) D6751 focused on acid value, flash point, water content and density. Fourier Transform Infrared Spectroscopy (FTIR) was used to examine chemical content and finding degradation. The samples were stored in three different storage temperatures and durations. Three phases have been designed in this study involving sample preparations, fuel properties experiment and engine performance test. The important finding obtained from this study is the HBL biodiesel fuel properties such as acid values, flash points, water content and density proportionally increase with the storage temperatures and durations. The blend samples of B70, B80 and B90 degrade over time as the storage duration increases. The temperature also plays significant roles to accelerate the degradation process. FTIR spectrum results show, small changes in seven weeks of storage had significant effect to the fuel properties especially for flash point and acid value. Due to technical limitation and difficulty, only B70 biodiesel have been experimented and showing similar engine performance curve as compared to the standard B5. After three weeks of storage duration, the B70 fuel degraded and the results from the engine torque and power curves show reduction. Further investigation is needed to analyse others biodiesel properties impact on storage durations and temperature to the engine performance.